Gallium labeled NOTA-based conjugates for peptide receptor-mediated medical imaging - Sá, Arsénio Vasconcelos (2010)
We report a straightforward and efficient synthetic strategy for the synthesis of three model glycine-arginine-glycine-aspartic-glycine (GRGDG) conjugates based on derivatives of NOTA and of their Ga(III) complexes targeted to the integrin αѵβ₃receptor. 71Ga NMR spectroscopy showed that the Ga(III)-labeled conjugates are highly stable in aqueous solution. The 67Ga-labeled conjugates proved to have high kinetic stability and showed a weak but specific binding to the receptors in a U87MG-glioblastoma cell line.